Transformative learning in a post-totalitarian context: professional development among school teachers in rural Siberia - Griswold, Wendy (Kansas State University, 2007)
This study focused on the professional development experiences of teachers in the Altai Republic, Russian Federation. Russia is a country in flux, transitioning from a totalitarian state into a democracy reflective of its unique ethnic composition, geographic context, and history. The Russian educational system is currently undergoing computerization and teachers are learning to integrate educational technology into classroom practice. In this setting, teachers are beginning to learn how to integrate educational technologies into their classroom practices. This qualitative study explored the potential for transformative learning associated with this type of learning and experience. Transformative learning theory (TLT) was used to explore if and how the world views and perspectives of teachers is changing with respect to their educational philosophies and classroom practice. The study utilized multiple sources of evidence (interviews with program and school administrators, school teachers, observation) and multiple units of analysis (federal/republic levels of training and support, school level training and support, informal experiences, teachers, administrators). Findings indicated that the methods used to train teachers have a high likelihood of being facilitative of transformative learning. It also found that teachers are beginning to think and act in new ways based on their experiences with educational technology. Teachers are also collaborating in this learning process, which provides an important support for continued learning and growth. Findings also indicate that TLT is a useful framework for exploring transformative learning in this setting and helped to uncover the elements of transformative learning which are culturally determined. Further research is needed to further our understanding of how transformation occurs and is experienced in this setting. Collaboration with local experts and researchers is necessary to uncover the cultural differences related to perspective change. Many future pathways are available for continuing to explore transformative learning in this context. They include continued work with teachers, a general exploration of transformative learning, and work with university students.
Keywords: Transformative learning theory; Adult education; Altai Republic, Russia; Siberia; School teachers; Educational technology; Education, Adult and Continuing (0516)